Control of electrical discharge machining servo system - Abd. Al-Ameer, Shuruq (2014)
Electrical discharge machining (EDM) is one of the earliest non-traditional machining processes. EDM process is based on thermoelectric energy between the work piece and an electrode. Material removal rate (MRR) is an important performance measure in EDM process. A servo system is employed which compare the gap voltage with reference value and to ensure that the electrode moves at a prepare rate to maintain the right spark gap, and also to retract the electrode if short circuiting occurs. For maintaining the gap between the electrode and the work piece in electrical discharge machining (EDM) system, the digital PID controller for DC motor via ARM microcontroller is proposed and implemented. The signal from the encoder-generator provides the speed and position information to the controller. PID controller system is implemented on ARM microcontroller to control the gap width between the electrode and work piece to get better performance for EDM process. A digital PID algorithm which makes the control system more flexible, robust and high performance is presented and applied in this control system.